2019
DOI: 10.1007/978-981-32-9563-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Big Data Adoption as a Marketing Tool in SMEs

Abstract: The change brought by Big Data about the way to analyze the data is revolutionary. The technology related to Big Data supposes a before and after in the form of obtaining valuable information for the companies since it allows to manage a large volume of data, practically in real time and obtain a great volume of information that gives companies great competitive advantages. The objective of this work is evaluating the factors that affect the acceptance of this new technology by small and medium enterprises. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…EE correlates BI [36], [37], [39]- [42], [45]. Alter in SI make BI transformed [38], [39], [41]- [43], [45]. FC factor can permute BI [39], [40], [42].…”
Section: B Forest Plot and Heterogeneitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…EE correlates BI [36], [37], [39]- [42], [45]. Alter in SI make BI transformed [38], [39], [41]- [43], [45]. FC factor can permute BI [39], [40], [42].…”
Section: B Forest Plot and Heterogeneitiesmentioning
confidence: 99%
“…Alter in SI make BI transformed [38], [39], [41]- [43], [45]. FC factor can permute BI [39], [40], [42]. FC factors affect the Use Behavioral factor [36], [38], [39].…”
Section: B Forest Plot and Heterogeneitiesmentioning
confidence: 99%
“…To review the previous study, the author focused on the studies which applied UTAUT and SMEs. UTAUT has been applied by many researchers to study DWP adoption in SMEs such as accounting information system (Lutfi, 2022); cloud computing technology (Khayer et al, 2021); e-commerce (Shahzad et al, 2020) & (Sombultawee, 2020); electronic procurement Kit et al (2021); Soong et al (2020) digital advertising (Reyes-Mercado & Barajas-Portas, 2020) ; enterprise system (Awa & Ukoha, 2020); social media (Alhaimer, 2019); smart manufacturing technology (Chei et al, 2019); big data (Silva et al, 2019); Internet technology adoption (Dasgupta & Gupta, 2019) and business application (Ibrahim et al, 2018) The environmental factor was a positive predictor of the performance expectancy of electronic commerce (EC) among SMEs, it does not, however, encourage the adoption of EC. The knowledge factor is a significant determinant of the adoption of EC among SMEs.…”
Section: Definition and Conceptualizations Of Digital Workplacementioning
confidence: 99%
“…Another study revealed that infrastructure is the most critical factor for BDA in SMEs. Additionally, possible problems for implementing BD in SMEs were discussed [24].…”
Section: Literature Reviewmentioning
confidence: 99%